Dark memories in the provincial words of Ingmar Bergman’s Fanny and Alexander and Federico Fellini’s Amarcord - Marklund, Anders (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Dark memories in the provincial words of Ingmar Bergman's Fanny and Alexander and Federico Fellini's Amarcord This article about Federico Fellini’s Amarcord (1973) and Ingmar Bergman’s Fanny and Alexander (1982) concerns one aspect of the directors’ childhood memories, namely how authoritarian institutions are used to disrupt otherwise fairly idyllic and nostalgic lives and worlds. The films blend detailed memories with playful fantasies, combine experiences of the directors’ alter egos, Titta and Alexander, with rituals of family and larger communities in the provincial cities of Rimini and Uppsala. In each film, bitter memories are given a central role. This article explores the similarities of these bitter memories, as they are imagined in the mature auteurs’ last exceptionally successful films.